The snow alga Chloromonas kaweckae sp. nov. (Volvocales, Chlorophyta) causes green surface blooms in the high tatras (Slovakia) and tolerates high irradiance - Procházková, Lenka; Matsuzaki, Ryo; Řezanka, Tomáš; Nedbalová, Linda; Remias, Daniel (Journal of phycology, 2023)
Seasonally slowly melting mountain snowfields are populated by extremophilic microalgae. In alpine habitats, high-light sensitive, green phytoflagellates are usually observed in subsurface layers deeper in the snowpack under dim conditions, while robust orange to reddish cyst stages can be seen exposed on the surface. In this study, uncommon surface green snow was investigated in the High Tatra Mountains (Slovakia). The monospecific community found in the green surface bloom consisted of vegetative Chloromonas cells (Volvocales, Chlorophyta). Molecular data demonstrated that the field sample and the strain isolated and established from the bloom were conspecific, and they represent a new species, Chloromonas kaweckae sp. nov., which is described based on the morphology of the vegetative cells and asexual reproduction and on molecular analyses of the strain. Cells of C. kaweckae accumulated approximately 50% polyunsaturated fatty acids, which is advantageous at low temperatures. In addition, this new species performed active photosynthesis at temperatures close to the freezing point showed a light compensation point of 126 ± 22 μmol photons · m-2 · s-1 and some signs of photoinhibition at irradiances greater than 600 μmol photons · m-2 · s-1 . These data indicate that the photosynthetic apparatus of C. kaweckae could be regarded as adapted to relatively high light intensities, otherwise unusual for most flagellate stages of snow algae.
Keywords: Slovenská republika; Chlorophyceae; Photosynthesis; fatty acids; nízká teplota; environmental sample; vegetative stages; Chlorophyta; fotosyntéza; biodiversity; cryoflora; fluorometry; Cold Temperature; Slovakia